Changing in lifestyle of people in tourist destinations zones - Bùi, Thanh Thủy (2021)
Almost researchers, practivists, managers in tourism have realized economic effects of tourism is the rooted reason the changes in living standards, lifestyle through concept, behavior, attitude, communication of local people and tourist. it may be that the change in lifestyle of people and tourist destinations is the indirect economic effectsb of tourism to them .